Methods used for facial morphology research - P. Kamínková (Czech Dental Chamber, 2019)
Introduction and aim of study: The human face serves as a source of a great deal of information. Knowledge of its morphology is essential for many biomedical specializations. The study of the face brings many difficulties. Problematic is the high facial shape variability as well as the fact that the individual parts grow with different speed. The purpose of this review of existing literature is to present research methods of the facial morphology and describe their advantages and disadvantages. Methods: Anthropometry belongs to traditional research methods. It deals with the measuring of size, weight and proportions of the human body. Although this way of research is inexpensive and three-dimensional, it is very time-consuming. In clinical practice, cephalometry and classical two-dimensional photographs are the most common methods used for facial structures analysis. The advantages of these two-dimensional imaging methods are a quick acquisition, a possibility of the obtained data storage and low cost. Recently, there has been a growing interest of many studies in three-dimensional imaging systems. These systems have been found useful not only in orthodontics but also in maxillofacial surgery. Computed tomography, cone-beam computed tomography, laser and optical scanners belong to these. The first two mentioned techniques are not suitable for research of facial morphology on account of exposure to radiation, high cost and low resolution of facial contours.Laser scanners use laser beam (point or stripe) that goes over the patient's face and creates a very accurate three-dimensional model. The time for its acquisition is relatively long (up to 20 seconds). Optical scanners can be divided into two groups according to the scanning principle: scanners using structured light and scanners using stereo photogrammetry (passive or active). The obtained models describe surface structures in detail with a realistic picture of a texture and skin colour. Conclusion: Three-dimensional photographs are constantly becoming more important in many fields (anthropology, genetics, orthodontics, surgery...). Their accuracy and potential in clinical practice have already been verified in independent studies.